Exposure to classroom sound pressure level among dance teachers in Porto Alegre (RS) - Nehring, Cristiane; Bauer, Magda Aline; Teixeira, Adriane Ribeiro (International Archives of Otorhinolaryngology, 2013)
Introduction: Dance teachers are exposed to high sound intensities. Aim: To verify the sound intensity of music used by dance teachers during classes. Method: This was a transversal and prospective study. Dance teachers were evaluated with a sociodemographic questionnaire, and sound intensity level measurements were taken at the beginning, middle, and end of dance classes. Results: The sample comprised 35 teachers (average age, 31.8 years). The duration of their career as dance teachers was 1–37 years; they worked daily for approximately 1–10 h. Among the classes followed, there were 15 (42.85%) classical ballet classes, 4 (11.42%) tap dancing lessons, 5 (14.28%) jazz dance classes, 2 (5.71) Arab dance lessons, 6 (17.14%) street dance classes, and 3 (8.57%) ballroom dancing lessons. The average values observed at the beginning, middle, and end of the classes were 80.91 dB (A), 83.22 dB (A), and 85.19 dB (A), respectively. The music played in the street dance classes exposed teachers to the highest sound intensity. Conclusion: The average level of sound intensity of the dance classes in this study was either below or equal to the limit considered harmful for hearing health. Analysis of different class types showed that the sound densities of street, ballroom, and tap dance classes were above the recommended limits.
Keywords: sound; noise effects; noise; occupational; noise effects